Racial Categorization Predicts Implicit Racial Bias in Preschool Children. Issue 1 (12th June 2017) - Setoh, Peipei; Lee, Kristy J. J.; Zhang, Lijun; Qian, Miao K.; Quinn, Paul C.; Heyman, Gail D.; Lee, Kang
Abstract : This research investigated the relation between racial categorization and implicit racial bias in majority and minority children. Chinese and Indian 3‐ to 7‐year‐olds from Singapore ( N = 158) categorized Chinese and Indian faces by race and had their implicit and explicit racial biases measured. Majority Chinese children, but not minority Indian children, showed implicit bias favoring own race. Regardless of ethnicity, children's racial categorization performance correlated positively with implicit racial bias. Also, Chinese children, but not Indian children, displayed explicit bias favoring own race. Furthermore, children's explicit bias was unrelated to racial categorization performance and implicit bias. The findings support a perceptual–social linkage in the emergence of implicit racial bias and have implications for designing programs to promote interracial harmony.